To test or not to test: COVID-19 prevention strategies to keep large satherings safe - Estelle, C. D.; Perl, T. M. (Annals of Internal Medicine, 2021)
Key nonpharmaceutical interventions (NPIs) implemented to minimize the spread of SARS-CoV-2 among the public were protective yet led to social isolation and other downstream effects. Although the COVID-19 pandemic lingers, many municipalities and regions are liberalizing NPI measures and restrictions to diminish the societal impact. Attempts to "open up" society include increasing public access to previously prohibited crowded indoor social gatherings. However, COVID-19 vaccines are still not universally available, wanted, or implemented. Health officials are therefore searching for strategies to effectively prevent SARS-CoV-2 transmission while allowing certain activities (such as concerts) to proceed, providing both desired psychosocial relief and economic benefits.